Characterisation of Cognitive Style involving Cultural Study from Ethnic Groups - Murkute, Suparna Aniruddha (JOURNAL OF INDIAN EDUCATION, 2021)
Research in education does not only represent a study of scholastic achievements of students but it is also a study of emotional and cultural endowments of students highlighting on their sense of responsibilities with their abilities to adjust and co-operate in a culturally diverse group or as suppported by society. In India, various cultural ideologies live together peacefully. The present study reveals that cultural groups still retain their cultural ideologies. The study also encompassed on the difference where the girls scored high in systematic cognitive style while boys were seen observing the step-by-step approach for solving problems to arrive at conclusions. The present study is carried out by implementing the ‘Cognitive Style Inventory’ by Praveen Kumar Jha.